Community governance with habitus in bonding to prevent SARS-CoV-2 pandemic transmission - Tiyas Nur Haryani (Journal of Social Studies (JSS), 2021)
Many areas at lowest level like kampong and village have initiatives in community governance terminology to prevent the SARS-CoV-2 transmission in their neighborhood formerly constituting green zone.  Community governance will be followed by bonding containing habitus inherent to society structure. This research was conducted in some villages throughout Surakarta Ex-Residency, involving observation and documentattion in Gatak, Banaran, Mojolaban Sub District of Sukoharjo Regency, Karangpandan Sub District of Karanganyar Regency and Kranggan Village of Polanharjo Sub District of Klaten Regency. Data was collected through interview, observation, and documentation. The result of study showed that innovation and productivity arose in community governance in Kranggan Village of Klaten Regency, as indicated with the presence of Karantani program. It is the planting or farming program for Persons under Surveillance or nomads (wanderers) going back to their village. Community leadership, community empowerment and community ownership arise in community governance in Kranggan Village. Furthermore, people should rekindle habitus related to embung (water reservoir), lumbung (communal rice barn), and saung (hut) post-pandemic considered as important in this Covid-19 pandemic period.